Measurement of improved singlet oxygen generations of indium chloride phthalocyanines by comparatively sono-photochemical and photochemical studies - Atmaca, Goknur Yasa; Karanlik, Ceren Can; Erdogmus, Ali (ELSEVIER SCI LTD, 2021)
Singlet oxygen quantum yield is known as a suitable measure to study the oxygen-producing capacity of a sono/ photosensitizing molecule. Its value significantly depends on the applied therapeutic method and the photophysicochemical properties of the molecule. To obtain a good sensitizer, this paper aims to synthesize highly soluble 3-[4-(4-fluoro-, chloro-, and bromo-phenoxy)phenoxy] substituted new indium phthlocyanines and then calculates the singlet oxygen generations by performing both photochemical and sono-photochemical methods in DMSO as a biocompatible solvent. The complexes showed higher singlet oxygen quantum yields (0.84 for InPc1, 0.89 for InPc2, and 0.94 for InPc3) by applying sono-photochemical methods compared to those (0.63 for InPc1, 0.67 for InPc2, and 0.80 for InPc3) were obtained by applying photochemical methods. These results show that the sono-photochemical methods improve the therapeutic activity in comparison to photochemical ones.
Keywords: Sono-photochemical; Photochemical; Indium phthalocyanine; Singlet oxygen; PHOTODYNAMIC THERAPY; PHOTOPHYSICOCHEMICAL PROPERTIES; CANCER; ZINC; Chemistry; Engineering; Materials Science